Clinical Implementation and Evaluation of Three Implementation Interventions for a Family-Oriented Care for Children of Mentally Ill Parents (ci-chimps): Study Protocol for a Randomized Controlled Multicenter Trial - Laser, Carolin; Modarressi, Anna; Skogøy, Bjørg Eva; Reupert, Andrea; Daubmann, Anne; Höller, Alexandra; Zapf, Antonia; Pawils, Silke; Taubner, Svenja; Winter, Sibylle; Maybery, Darryl; Wiegand-Grefe, Silke (Frontiers in Psychiatry, 2022)
Background In Germany, approximately three million children under the age of eighteen have a mentally ill parent. These children are at an increased risk of developing a mental illness themselves (1) as well as a physical illness (2). While research has identified numerous evidence-based family-oriented interventions, little is known about how to implement such interventions effectively and efficiently in clinical practice in Germany. This implementation study (ci-chimps) evaluates three clinical implementation projects with three different implementation interventions for the optimal implementation of the tailored family-oriented preventive and therapeutic interventions in the CHIMPS-NET (children of mentally ill parents—research network) with an implementation model for children of mentally ill parents. Methods A two-group randomized controlled multicenter trial will examine changes in family-oriented practice and aspects of implementation at baseline as well as at 12- and 24-months follow-up. The CHIMPS-Network consists of 20 clinical centers. The centers in the intervention group receive the support of all of the three implementation interventions: (1) optimal pathways to care, (2) education and a training program for professionals, and (3) systematic screening for children. The centers in the control group do not receive this specific implementation support. Discussion While we know that children of mentally ill parents are an important target group to be addressed by preventive and therapeutic interventions, there is often a lack of structured implementation of family-oriented interventions in clinical practice in Germany. Using a randomized controlled multicenter trial design with a large and wide-ranging sample (clinics for adult psychiatry and clinics for child and adolescent psychiatry, university clinics and clinics at the real health care) will provide a robust understanding of implementing family-oriented changes in German clinical practice. Trial Registration The CHIMPS-NET-study was registered with the German Clinical Trials Register on 2019-12-19 (DRKS00020380) and with Clinical Trials on 2020-4-30 (NCT04369625), the ci-chimps-study was registered with the German Clinical Trials Register (DRKS00026217) on 2021-08-27, the Clinical Trials registration is in review process.